A comparative study of HPLC-UV and UPLC-DAD methods for simultaneous estimation of aspirin and cilostazol in the presence of their related impurities in bulk and capsules. Issue 4 (25th February 2017) - Elkady, Ehab Farouk; Tammam, Marwa Hosny; El Maaty, Ayman Abo
ABSTRACT: Aspirin (ASP) and cilostazol (CST) are used as a combination in pharmaceutical formulations for treatment of strokes. Salicylic acid (SAL) is considered to be one of the main synthesis impurities and a degradation product of ASP. On the other hand, the main related impurities of CST are CST related A, B, and C (CST-RA, CST-RB, and CST-RC), respectively. Furthermore, as high efficiency and less elution are the basic requirements of high-speed chromatographic separation, so, a comparative study of two simple, precise, and accurate reversed-phase HPLC and UPLC methods was developed and validated for simultaneous estimation of ASP and CST in bulk and capsules in the presence of SAL, CST-RA, CST-RB, and CST-RC. A Eurospher II C18 (250 × 4.6 mm 2, 5 µm) for HPLC method and an Agilent Zorbax Eclipse Plus C18 (50 × 2.1 mm 2, 1.8 µm) for UPLC method were used. A gradient mobile phase of 20 mM anhydrous KH2 PO4 buffer solution (containing 0.2% triethylamine (TEA), v/v) with pH adjusted to 2.9 using orthophosphoric acid (solution A) and acetonitrile (solution B) mixed in different proportions for HPLC and UPLC methods was prepared. Flow rate was set to 1.0 and 0.3 mL min −1 for HPLC and UPLC methods, respectively, and the detection was performed for both methods at 210 nm. It worth noting that the proposed UPLC-DAD assay exhibited relatively much more precision, sensitivity, specificity, and economic and chromatographic separation superiority than proposed HPLC-UV assay. Both developed methods were compared with reference methods to prove its applicability and are suitable for purity assessment of ASP and CST in bulk and capsules. GRAPHICAL ABSTRACT: